Acupuncture for dry eye syndrome after refractive surgery: A randomized controlled pilot trial - Jun-Hwan Lee; Kyungsun Han; Tae-Hun Kim; Ae-Ran Kim; Ojin Kwon; Joo-Hee Kim; Jeong-Eun Kim; Seunghoon Lee; Mi-Suk Shin; So-Young Jung; Hyo-ju Park; Sanghun Lee (Integrative Medicine Research)
Background: Dry eye syndrome is the most common complication of refractive surgery. Acupuncture is widely used for the treatment of ophthalmologic diseases, but to date, few have explored the effects of acupuncture for the treatment of this condition following refractive surgery. The objective of this study is to assess the feasibility of a study design for evaluating the effectiveness of acupuncture treatment along with usual care compared with usual care only for dry eye syndrome after refractive surgery. Methods: A total of 18 patients with dry eye syndrome occurring after refractive surgery participated in this study. For 4 weeks, the acupuncture plus usual care and usual care only groups received treatment three times a week. A series of assessments, namely the ocular surface disease index (OSDI), visual analog scale for ocular discomfort, quality of life, tear film break-up time, Schirmer 1 test, and fluorescein-stained corneal-surface photography, along with other general assessments were carried out. Results: Although preliminary, changes in OSDI from the baseline values were significantly different between the two groups at week 5 (p = 0.0003). There was a significant difference in the trends of OSDI changes between the acupuncture plus usual care and the usual care only groups (p = 0.0039). No serious adverse events were reported during the study. Conclusion: Four weeks of acupuncture treatment in addition to usual care is a feasible treatment for dry eye syndrome after refractive surgery. A full-scale randomized controlled trial is needed to confirm the clinical effectiveness of acupuncture.